Quantitative Analysis of Flavonoids and Coumarins from Fingered Citron in Different Growth Periods and Their Regulatory Effects on Oxidative Stress - Tao Tan; Man Xu; Xianlong Hong; Zhenyuan Li; Jiangnan Li; Bining Jiao; Xijuan Zhao (Foods)
Twenty-two coumarins and twenty-six flavonoids were quantitated in fingered citron in different growth periods. Limettin was the top coumarin, and diosmin was the highest flavonoid, followed by hesperidin. Antioxidant evaluation by DPPH, ABTS, and FRAP indicated extracts of fingered citron in three growth periods all showed good antioxidant activity, which was positively correlated with the concentration of extracts. The oxidative stress model of RAW264.7 cells indicated extracts from fingered citron effectively reduced the contents of NO, MDA, and ROS in cells and increased the activity of SOD, thereby alleviating cell damage. The antioxidant capacity of fingered citron in November was the highest, followed by July and September. And there was a significantly positive correlation between the total flavonoid content and the antioxidant capacity. Diosmin, hesperidin, and neohesperidin were the main contributors to antioxidation. This study has significance for utilization of fingered citron germplasm resources and development of related functional products.